Органические светоизлучающие структуры — технологии XXI века - Sorokin, V. M; Kolomzarov, Yu. V.; Maslak-Gudima, N. P.; Minyajlo, M. A. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
The presented review suggests that solving the complex of technological, materials science, and technical problems in the development of modern OLED and PLED devices within the next 5–10 years will lead to the creation of instruments with energy efficiency exceeding 100 lm/W and a service life of up to 100,000 hours. Achieving such parameters will make it possible to expand the application scope of the systems under consideration and to create in the future unique flat, energy-efficient organic lighting systems of a new generation — the light sources of the 21st century.